Effect of Tamoxifen on Hepatic Regeneration in Male Rats - KAHN, D. (1989)
A number of metabolic changes within the liver occur concurrent with hepatic regeneration. These processes suggest that the administration of an antiestrogen might alter the rate of hepatic regeneration. To examine this question, male Wistar rats were treated with tamoxifen (0.1 mg/rat/day or 1.0 mg/rat/day) or vehicle for three days prior to and after partial hepatectomy, and the anatomic and biochemical process of hepatic regeneration was assessed. Tamoxifen administration caused a dose-dependent decrease in the hepatic cytosolic estrogen receptor activity and, conversely, a dose-dependent increase in cytosolic androgen receptor activity. Despite these changes in baseline hepatic sex steroid receptor status, all receptor activities were comparable between the three groups within 24 hr of partial hepatectomy. Moreover, no differences in any of the the parameters assessing hepatic regeneration following partial hepatectomy were evident: liver–body ratio, ornithine decarboxylase activity, and thymidine kinase activity. This lack of effect of tamoxifen treatment on hepatic regeneration suggests either that estrogens do not play a role in the modulation of liver growth after partial hepatectomy or that, once initiated, the regenerative process per se determines a series of events that regulate hepatocellular sex hormone receptor status independent of extrahepatic stimuli.